Twenty-five years of mainstreaming gender in development: A review - Bans-Akutey, Anita (Journal of Social, Humanity, and Education, 2025)
Purpose: This review examines the global progress and challenges of gender mainstreaming in development from 1999–2024. It evaluates how gender perspectives have been integrated into policy, institutional frameworks, and sectoral development efforts to achieve gender equality and sustainable development outcomes. Research Methodology: This study employs a systematic literature review to analyze scholarly articles, policy reports, and institutional documents. It categorizes findings based on policy frameworks, institutional mechanisms, sectoral impacts, and regional variations, while drawing insights from Africa, Asia, Europe, Latin America and the Caribbean, the Middle East and North Africa, and North America. Results: The review identified significant progress in adopting gender-sensitive policies and institutional mechanisms worldwide. However, challenges persist, including policy implementation gaps, sociocultural barriers, inadequate funding, and varying regional effectiveness. While some regions have advanced gender equality in governance and economic participation, others still face systemic constraints on women’s participation. Conclusions: Although significant strides have been made in integrating gender perspectives into development frameworks since 1999, persistent structural and institutional challenges continue to hinder the full realization of gender equality and sustainable development goals. Limitations: This study did not account for the detailed country-specific challenges of all countries worldwide. Contribution: The findings highlight the need for more intersectional and localized gender-mainstreaming strategies, stronger monitoring and evaluation systems, and enhanced collaboration among stakeholders to bridge policy-practice gaps.